Perluasan Kompetensi Absolut Pengadilan Tata Usaha Negara dalam Undang-Undang Administrasi Pemerintahan - Ridwan HR; Despan Heryansyah; Dian Kus Pratiwi (Jurnal Hukum IUS QUIA IUSTUM, 2018)
This study focused on the extension of the absolute competence of the State Administrative Court (PTUN) in Law Number 30 of 2014. This study had two objectives, first, the extension of the absolute competence of PTUN and second, the implications on the extension of the absolute competence of PTUN. This study used normative legal method, where the da. The results showed that there are several forms of extension of absolute competence ta were enriched by conducting interviews with PTUN judges in several regions in Indonesiaof PTUN, such as the authority to examine factual conducts, examine abuse of authority, examine administrative efforts, examine legally accepted decisions, and examine discretion. Meanwhile, an implication after the enactment of this law on the legal system in Indonesia is there are a number of articles which are not only ambiguous, but also contradict the doctrines and theories of administrative law that has long been adopted by administrative law experts